Perceptions of Residents Living in Sultanahmet Towards Tourism - Aydın, Çağdaş; Aydın, Ceren; Kozak, Nazmi (Istanbul University, 2024)
This study identified the perceptions and attitudes of residents living in the Sultanahmet area of Istanbul regarding tourism. The perceptions and attitudes of the residents towards tourism were analysed within the framework of the Social Exchange Theory. The study interviewed 18 individuals, including residents and business owners from the Sultanahmet area. A qualitative approach was adopted for the study, and the data have been analysed using content analysis. The participants’ perceptions of tourism were categorised under three main headings: economic, sociocultural, and environmental. While the participants emphasised the financial contributions of tourism, they also focused on the negative environmental impacts of tourism. Sultanahmet’s residents mainly perceived the socio-cultural effects of tourism positively. The results of this study are expected to shed light on tourism planning and the development of appropriate strategies for the region, which could benefit relevant authorities.
Keywords: Geography (General); sultanahmet; Beşeri Coğrafya (Diğer); hippies; residents’ tourism perceptions; G1-922; Social Exchange Theory; Hippies; Residents’ tourism perceptions; Sultanahmet; Türkiye; türkiye; Human Geography (Other); social exchange theory; 11. Sustainability